(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Cancer diagnosis is a life-altering experience, affecting not only an individual’s physical healthbut also their emotional and psychological well-being. This study examines the impact of self-consciousemotions on social readjustment and psychological well-being among women cancer patients in Dubai.It delves into the strategies employed by patients to regulate these self-conscious emotions and theirrole in social adaptation and psychological well-being. Research uses sample of 60 women cancerpatients. This study is quantitative in nature. The findings of the study uncovers those self-consciousemotions has significant effect on social readjustment, and psychological well-being. It emphasizes theneed for holistic support programs that address the emotional needs of cancer patients, offeringpractical insights for healthcare providers and policymakers. The findings provide a valuablecontribution to the field of cancer support and care, offering a deeper understanding of the emotionalexperiences of women cancer patients in Dubai and suggesting directions for future research andintervention strategies.